2022
DOI: 10.1371/journal.pone.0263534
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of peritoneal dialysis in elderly vs non-elderly patients: A systemic review and meta-analysis

Abstract: Objectives Several studies have compared outcomes of peritoneal dialysis (PD) between elderly and non-elderly patients but with variable results. We hereby designed this review to compare mortality, peritonitis, and technique survival between elderly and non-elderly patients on PD. Methods PubMed, Embase, and Google Scholar were searched for studies comparing outcomes of PD between elderly and non-elderly patients. The last search date was 14th July 2021. Results Fourteen studies were included. 12 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As a result of global increases in life expectancies, the number of older people (≥65 years old) commencing dialysis is growing 232 . Despite the potential advantages of PD listed in the introduction of this review, older patients face several potential barriers to accessing PD, including frequent late presentation, comorbidities, frailty, functional dependence, impaired dexterity, impaired visual acuity and reduced cognitive function 233 , 234 . A systematic review and meta-analysis of 14 non-randomized studies from 13 countries in Europe, Asia, Latin America and Oceania between 2000 and 2021 reported that (with low-certainty evidence) PD in older patients might be associated with higher mortality (relative risk (RR) 2.45, 95% CI 1.36–4.40, P = 0.003, I 2 = 97%) and more frequent peritonitis (RR 1.56, 95% CI 1.18–2.07, P = 0.002, I 2 = 76%); differences in technique survival between older and younger patients were minimal or absent (RR 0.95, 95% CI 0.86–1.05, P = 0.32, I 2 = 86%) 233 .…”
Section: Pd Outcomes In Vulnerable Populationsmentioning
confidence: 99%
“…As a result of global increases in life expectancies, the number of older people (≥65 years old) commencing dialysis is growing 232 . Despite the potential advantages of PD listed in the introduction of this review, older patients face several potential barriers to accessing PD, including frequent late presentation, comorbidities, frailty, functional dependence, impaired dexterity, impaired visual acuity and reduced cognitive function 233 , 234 . A systematic review and meta-analysis of 14 non-randomized studies from 13 countries in Europe, Asia, Latin America and Oceania between 2000 and 2021 reported that (with low-certainty evidence) PD in older patients might be associated with higher mortality (relative risk (RR) 2.45, 95% CI 1.36–4.40, P = 0.003, I 2 = 97%) and more frequent peritonitis (RR 1.56, 95% CI 1.18–2.07, P = 0.002, I 2 = 76%); differences in technique survival between older and younger patients were minimal or absent (RR 0.95, 95% CI 0.86–1.05, P = 0.32, I 2 = 86%) 233 .…”
Section: Pd Outcomes In Vulnerable Populationsmentioning
confidence: 99%
“…Patients, carers and clinicians also remain unaware of the relative benefits and harms of each option or the costs. For instance, PD was less likely to be discussed with the elderly or those with higher BMI, but studies have shown superior outcomes in patients with higher BMI36 and age has not been shown to impact on technique survival 37…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PD was less likely to be discussed with the elderly or those with higher BMI, but studies have shown superior outcomes in patients with higher BMI 36 and age has not been shown to impact on technique survival. 37 …”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges that may influence provider perceptions towards home dialysis is that some studies have suggested outcomes are worse, especially amongst older adults receiving PD. It has been shown that older PD patients are at a higher risk of mortality (pooled relative risk 2.45, 95% confidence interval 1.36–4.40) versus younger PD patients [ 26 ]. When comparing across modalities, outcomes among older adults differ.…”
Section: Prioritizing and Optimizing Outcomes For Older Adults Receiv...mentioning
confidence: 99%